Materials for future gas turbine applications. (December 2014) - Rugg, D.
Abstract : The complexity of adopting new or using existing advanced alloy systems in demanding environments where safety is paramount is highlighted. Of particular importance is the ability to define operative deformation and degradation mechanisms that may limit part life or functionality. With respect to the underlying fundamental material science there is a high degree of commonality between the aero and power generation sectors. The vast array of new experimental and modelling techniques that can be brought to bear on long standing technical challenges offers the potential for a renaissance in materials science. Of particular interest from an industrial context would be the ability to 'design' material microstructure and texture optimised for service use manufactured via the most energy and time efficient route. The requirements and potential for progress in this area is summarised with an emphasis on gas turbine and nuclear reactor applications for hcp metals.